Spatially uneven mitigation effects of digital financial inclusion on carbon emissions in China - Leying Wu (3937943) (2025)
At the COP28 UN climate change conference, pivotal initiatives spotlighted the potential of digital financial inclusion (DFI) in mitigating carbon emissions. However, the impact of DFI on CO2 emissions and its underlying mechanisms remain insufficiently explored. Leveraging county-level panel datasets, we employ a spatiotemporal econometric model to examine the spatially uneven effects of DFI on CO2 emissions, while controlling for diverse natural and socioeconomic factors. Results show a significant mitigation effect of DFI on CO2 emissions, which is consistent across various model specifications. Specifically, a 0.1-unit increase in DFI is associated with an approximate 41% reduction in CO2 emissions, with 2.1% attributable to direct effects and 38.9% resulting from indirect or spatial spillover effects. Furthermore, we identify substantial heterogeneities in the effects of DFI across geography and developmental stages of DFI, highlighting the importance of context-specific dynamics. Key mediators in the DFI – CO2 emissions link include economic growth, industrial restructuring, and progress in environmental technology. These findings provide valuable insights for the design of financial instruments to advance sustainable development goals and combat climate change.